1987
DOI: 10.1016/0741-5214(87)90034-6
|View full text |Cite
|
Sign up to set email alerts
|

Primary graft infections

Abstract: An amputation rate of 8% to 52% and a mortality rate of 13% to 58% make vascular prosthetic graft infections the most dreaded complication facing a vascular surgeon. In 1978 a randomized prospective double-blind study reported a statistically significant decrease in wound infections in patients treated with prophylactic antibiotics whereas the graft infection difference only approached statistical significance. The present study reviews 2614 arterial prosthetic grafts implanted from January 1975 through June 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0
2

Year Published

1988
1988
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(52 citation statements)
references
References 11 publications
1
49
0
2
Order By: Relevance
“…11 However, prior studies looking at graft infections have not analyzed if graft infection is an independent predicator of major lower extremity amputation. 4,5,10,11 Cryopreserved veins are an alternative conduit option to avoid amputation that has been reported with some success. 19 We did not use it in this study period, however we have subsequently used it with short term success.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…11 However, prior studies looking at graft infections have not analyzed if graft infection is an independent predicator of major lower extremity amputation. 4,5,10,11 Cryopreserved veins are an alternative conduit option to avoid amputation that has been reported with some success. 19 We did not use it in this study period, however we have subsequently used it with short term success.…”
Section: Discussionmentioning
confidence: 99%
“…2, 3 These surgical site infections occasionally lead to graft infection with rates of post-operative amputation and mortality as high as 52% and 58% respectively having been reported. 4 These prosthetic graft infections are not infrequent with a reported incidence of up to 4.7%. 5 Aside from the adverse effect on the patient, post-operative vascular surgical infections significantly contribute to health care costs, as they often require additional procedures and a lengthier inpatient stay.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This phenomenon may reflect a higher prevalence of other diseases, such as comorbidities, among patients admitted with AMI. In fact, some studies have already identified a higher prevalence of diabetes mellitus associated with AMI 3 , which in turn may increase the incidence of infectious complications in AMI, as with other diseases that affect elderly and/or diabetic patients 4,5,6,7 .…”
mentioning
confidence: 99%